Acidity-triggered charge-reversible multilayers for construction of adaptive surfaces with switchable bactericidal and bacteria-repelling functions. Issue 45 (25th October 2018) - Wu, Jindan; Zhao, Sufang; Xu, Shuting; Pang, Xiaoyu; Cai, Guoqiang; Wang, Jiping
Abstract : Microenvironment acidity of infected sites was utilized to control the surface charge, and therefore, manipulate bacterial behavior. Abstract : The acidity of a microenvironment in infected sites was utilized as the trigger to manipulate the bacterial behavior on the surface. Multilayers composed of dopamine-anchored poly(acrylic acid) (PAA-dopa) and chitosan quaternary ammonium salt (Q-CS) were deposited onto a surface via the layer-by-layer (LBL) assembly technology. The multilayer was crosslinked through the reaction of catechol moieties. The surface charge of the multilayer reversibly shifted from positive to negative as the pH increased without influencing the chemical composition and wettability of the top layer. The precise manipulation of the surface charge, and therefore, the biological function was achieved by varying the acidity. The bactericidal efficiency increased 15 times for E. coli, while almost 90% dead S. aureus and 100% E. coli were released from the surface when the pH increased from 5.0 to 7.4. Therefore, the functional surface was regenerated, which is particularly essential during the long-term treatment of chronic wounds. This study presented a new adaptive material responding to microenvironment acidity of the infected sites for efficient and safe antibacterial therapies.